The Importance of Pedagogical Competence in an Artificial Intelligence-Based Curriculum Towards the Golden Era of Indonesia 2045 - Rahma Aulia; Rindu Bunga Kasih; Wiwin Luqna Hunaida (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to explore the strategies and roles of teachers in the success of an artificial intelligence (AI)-based curriculum by strengthening pedagogical competencies to improve the quality of education towards the vision of Golden Indonesia 2045. The method used is library research with content analysis of secondary sources such as journals, books, policy documents, and academic databases (Google Scholar, Garuda, Scopus). The results show that teacher pedagogical competencies, including student understanding, learning design, technology utilization, and evaluation, are key to optimizing the AI curriculum. However, challenges such as the low increase in pedagogical competency (0.23) and the digital infrastructure gap hinder implementation. Proposed solutions include teacher training, development of an adaptive AI platform, collaboration with the technology industry, and integration of critical pedagogical approaches to shape a competitive generation. This study concludes that the synergy between teacher pedagogical competencies and the AI curriculum can create personalized, innovative, and relevant learning to meet the needs of the digital era, while supporting the development of superior human resources for Golden Indonesia 2045.